Generic realignments in Maxillariinae (Orchidaceae): Corrigenda et adenda - Blanco, Mario A; Carnevali, German; Witten, W. Mark; Singer, Rodrigo B.; Koheler, Samantha; Williams, Norris H.; Ojeda, Isidro; Neubig, Kurt M.; Endara, Lorena (Lankesteriana: International Journal on Orchidology, 2008)
Correction of Maxillaria bomboizensis: it proposes the synonym Sauvetrea bomboizensis. Year correction of Ponera adendrobium, 1964. Inclusion of: Camaridium carinulatum and Ornithidium fasciculatum.